Shaping financial futures: How does quran surah Yusuf discuss the instruments of the state financial policy? - Berkah, Dian; Widiastuti, Tika; Atiya, Nikmatul (al-Uqud : Journal of Islamic Economics, 2024)
This research presents an in-depth analysis of state financial policy, taking inspiration from the interpretation of the Prophet Yusuf's dream immortalised in Surah Yusuf. Using a qualitative approach and a literature review method that combines tafsir bi al ma'tsur and tafsir bi ra'yi, this research discusses each verse in detail, exploring the relevance of the findings to current scientific developments. The main findings include the seven-year cycle, the basis for formulating state financial policies, instruments based on food security strategies, and the determining phases for a country that can prosper or decline. This conclusion underlines the importance of the first and second cycles as policy foundations that should be addressed, opening new insights into understanding and designing state financial policies.